Policy integration: Do laws or actors integrate issues relevant to flood risk management in Switzerland?. (March 2020) - Metz, Florence; Angst, Mario; Fischer, Manuel
Highlights: Ecological systems often span several issues. In this paper, we consider 11 issues related to flood risk management such as habitat loss, delimitation of watercourse corridors hydropower operation impacts, revitalization, flood protection concepts, or technical flood protection. These issues are typically addressed in different policy sectors but exhibit ecological, functional, or geographical interdependencies. Integration between these issues is an important challenge for the successful governance of ecological systems. We analyze two bases for issue integration: a) political actors connecting issues and, b) the legal framework cross-referencing issues. We propose a network method for systematic comparisons between issue integration based on actors and integration based on laws. For the case of Swiss flood risk management, we find that actor- and law-based issue integration co-vary and might be self-reinforcing. We further find that issue integration mostly rests on laws, although cases exist where actors are the main basis of integration. Even if legal framework fails to integrate issues, actors make up for this in some cases. Favorable conditions for this to occur are especially given if actors are a relatively homogenous group. Abstract: Existing research emphasizes interdependencies between social and ecological systems in climate change adaptation. Ecological systems are often complex and span several issues that are not integrated in the social governance system. In order to increase the fit between social and ecological systems, understanding factors that promote the integration of interdependent issues is crucial. In this paper, we consider 11 issues related to flood risk management, e.g., technical flood protection and habitat loss, which are typically addressed in different policy sectors but exhibit ecological, functional, or geographical interdependencies. We analyze two bases for issue integration: a) political actors connecting issues and, b) the legal framework cross-referencing issues. We propose a network method for systematic comparisons between issue integration based on actors and integration based on laws. For the case of Swiss flood risk management, we find that actor- and law-based issue integration co-vary and might be self-reinforcing. We further find that issue integration mostly rests on laws, although cases exist where actors are the main basis of integration. Results promote our understanding of potential bases for the integration of policy issues, thereby contributing knowledge about adaptive governance capacities in social-ecological systems that buffer the effects of climate change.